Swarm observations of field‐aligned currents associated with pulsating auroral patches. Issue 11 (18th November 2015) - Gillies, D. M.; Knudsen, D.; Spanswick, E.; Donovan, E.; Burchill, J.; Patrick, M.
Abstract: We have performed a superposed epoch study of in situ field‐aligned currents located near the edges of regions of pulsating aurora observed simultaneously using ground‐based optical data from the Time History of Events and Macroscale Interactions during Substorms (THEMIS) all‐sky imager (ASI) network and magnetometers on board the Swarm satellites. A total of nine traversals of Swarm over regions of pulsating aurora identified using THEMIS ASI were studied. We determined that in the cases where a clear boundary can be identified, strong downward currents are seen just poleward and equatorward of the pulsating patches. A downward current in the range of 1–6 μA/m 2 can be seen just poleward of the boundary. A weaker upward current of 1–3 μA/m 2 is observed throughout the interior of the patch. These observations indicate that currents carried by precipitating electrons within patches could close through horizontal currents and be returned at the edges, in agreement with Oguti and Hayashi (1984) and Hosokawa et al. (2010b). In addition to confirming these earlier results and adding to their statistical significance, the contribution of this study is to quantify the upward and downward current magnitudes, in some cases using two satellites traversing the same pulsating regions. Finally, we compare Swarm's two‐satellite field‐aligned current product to the single‐satellite results and determine that the data product can be compromised in regions of pulsating aurora, a phenomenon that occurs over widespread regions and tends to persist for long periods of time. These results underscore the importance of electrical coupling between the ionosphere and magnetosphere in regions of patchy pulsating aurora. Key Points: Superposed epoch study of in situ field‐aligned currents within pulsating aurora We quantify the current magnitudes with in situ multisatellite observations Two‐satellite FAC product can be compromised in regions of pulsating aurora